2016
DOI: 10.1038/srep38589
|View full text |Cite
|
Sign up to set email alerts
|

All-Silicon Ultra-Broadband Infrared Light Absorbers

Abstract: Absorbing infrared radiation efficiently is important for critical applications such as thermal imaging and infrared spectroscopy. Common infrared absorbing materials are not standard in Si VLSI technology. We demonstrate ultra-broadband mid-infrared absorbers based purely on silicon. Broadband absorption is achieved by the combined effects of free carrier absorption, and vibrational and plasmonic absorption resonances. The absorbers, consisting of periodically arranged silicon gratings, can be fabricated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…The absorption around this resonance gets significantly broadened due to the high loss of Ti, which lowers the Q‐factor of the waveguide cavity. To date, other refractory metals as Ti have also been demonstrated for broadband absorption and semiconductors such as silicon (Si) and germanium (Ge) can be included instead of transparent insulators for extra absorption improvement . Interestingly, an additional propagating surface plasmon resonance (PSPR) excited at the short wavelength (Figure d,g,i) due to the relatively large Ti pattern period further boosted the absorption as presented by the other absorption peak at 914 nm in Figure b.…”
Section: Broadband Perfect Absorbersmentioning
confidence: 99%
“…The absorption around this resonance gets significantly broadened due to the high loss of Ti, which lowers the Q‐factor of the waveguide cavity. To date, other refractory metals as Ti have also been demonstrated for broadband absorption and semiconductors such as silicon (Si) and germanium (Ge) can be included instead of transparent insulators for extra absorption improvement . Interestingly, an additional propagating surface plasmon resonance (PSPR) excited at the short wavelength (Figure d,g,i) due to the relatively large Ti pattern period further boosted the absorption as presented by the other absorption peak at 914 nm in Figure b.…”
Section: Broadband Perfect Absorbersmentioning
confidence: 99%
“…In recent years, the silicon nanostructure has drawn increasing attention due to its ability to support plasmon resonance in the optical regime [ 29 , 30 , 31 , 32 , 33 , 34 ]. Silicon is one of feasible high refractive index materials that has been widely used to design optical devices, such as solar cells [ 29 ], detectors [ 30 ], color filters [ 31 , 32 ], photonic waveguides [ 33 ], and absorbers [ 34 ]. It has been demonstrated that this plasmon resonance in the silicon nanostructure could be tuned to enhance light absorption in the infrared and visible ranges [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon is one of feasible high refractive index materials that has been widely used to design optical devices, such as solar cells [ 29 ], detectors [ 30 ], color filters [ 31 , 32 ], photonic waveguides [ 33 ], and absorbers [ 34 ]. It has been demonstrated that this plasmon resonance in the silicon nanostructure could be tuned to enhance light absorption in the infrared and visible ranges [ 34 , 35 , 36 , 37 ]. The silicon-based PPA is easy to integrate into mature compatible complementary metal-oxide-semiconductor (CMOS) technology [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations